2018
DOI: 10.1159/000488735
|View full text |Cite
|
Sign up to set email alerts
|

Crocin Improves the Endothelial Function Regulated by Kca3.1 Through ERK and Akt Signaling Pathways

Abstract: Background/Aims: Based on the protective effect of crocin against cardiovascular diseases, we hypothesize that crocin could improve endothelial function through activating the eNOS(endothelial nitric oxide synthase) /NO pathway and/or the intermediate-conductance Ca2+-activated K+ channels (KCa3.1). Methods: In this study, rat aortic rings were used to assess the regulatory effect of crocin on vascular tone and nitric oxide, prostacyclin, and KCa3.1, all endothelial vasodilators, were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
4
9
0
Order By: Relevance
“…Antioxidants can cause diminished NO production by damage induction to the nitride oxide system (protein enzymes, substrates, and cofactors) (10). The results of a study by Kim et al is in line with the results of the present research, suggesting that Cro causes inhibition of NOinducing lipopolysaccharide through inducing expression of HO-1 and Calmodulin-calcium-dependent kinase-4 protein (32).…”
Section: Discussionsupporting
confidence: 91%
“…Antioxidants can cause diminished NO production by damage induction to the nitride oxide system (protein enzymes, substrates, and cofactors) (10). The results of a study by Kim et al is in line with the results of the present research, suggesting that Cro causes inhibition of NOinducing lipopolysaccharide through inducing expression of HO-1 and Calmodulin-calcium-dependent kinase-4 protein (32).…”
Section: Discussionsupporting
confidence: 91%
“…This strongly suggests the role of saffron and crocin in attenuating atherogenesis. These results are consistent with the findings reported by other investigators using its active compound, crocin, which improved endothelial function via extracellular receptor kinase (ERK) and protein kinase B (or also known as Akt) signalling pathways in HUVECs(19).…”
Section: Discussionsupporting
confidence: 92%
“…Crocin, as a typical flavonoid, has antiviral, hypoglycemic, hypotensive, immunomodulatory, and cardiovascular protective activities [39][40][41]. In recent years, studies have shown that crocin has protective effects against alcoholinduced neurological damage in mice.…”
Section: Neural Plasticitymentioning
confidence: 99%